2006
DOI: 10.1152/ajprenal.00395.2004
|View full text |Cite
|
Sign up to set email alerts
|

PMA- and ANG II-induced PKC regulation of the renal Na+-HCO3cotransporter (hkNBCe1)

Abstract: The renal electrogenic Na(+)-HCO3- cotransporter (hkNBCe1) plays a major role in the bicarbonate reabsorption by the kidney. We examined how PMA- and ANG II-activated PKCs regulate hkNBCe1 expressed with or without the ANG II receptors AT(1B) in Xenopus laevis oocytes. We found that 10 nM PMA halved the hkNBCe1 current detected in voltage-clamped oocytes. A PKC-specific inhibitor GF-109203X, and a specific inhibitor of Ca-dependent conventional PKCalphabetagamma, GO-6976, significantly reduced PMA inhibition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Investigators have reported that phosphorylation by activated PKA (3,4) or an increase in cytosolic Ca 2ϩ (5) can change the Na:HCO 3 Ϫ stoichiometry of the transporter. In addition, both cAMP (3) and ATP (6) appear to stimulate an NBC-mediated current, whereas PKC isoforms inhibit transporter activity (7).…”
mentioning
confidence: 99%
“…Investigators have reported that phosphorylation by activated PKA (3,4) or an increase in cytosolic Ca 2ϩ (5) can change the Na:HCO 3 Ϫ stoichiometry of the transporter. In addition, both cAMP (3) and ATP (6) appear to stimulate an NBC-mediated current, whereas PKC isoforms inhibit transporter activity (7).…”
mentioning
confidence: 99%
“…We (43,44) reported earlier that signaling via the angiotensin receptor (AT 1 R) stimulates endocytosis and inhibits functional activity of NBCe1 in Xenopus oocytes. Here, we expanded our early observations to investigate regulation of the surface expression of NBCe1 and NBCn1 in untreated and cholinergically stimulated parotid acinar cells.…”
mentioning
confidence: 99%
“…Female Xenopus laevis frogs (NASCO) were anesthetized with 1.5 mg/ml tricaine. The ovarian lobes were surgically removed, dissected, and treated with 2 mg/ml collagenase type IA, and oocytes were incubated as described previously (43,44). The cDNAs encoding human NBCe1 and M3R receptors were each subcloned into the pGH19 expression vector.…”
mentioning
confidence: 99%
See 2 more Smart Citations